Professional Deficiencies in Mathematics Teachers: An Analysis of Regional Research Results - Nazarov Xolmo’min Abduvahobovich (Euro Asian Journal Publishing, 2024)
Purpose: to describe the results of a regional study of subject and methodological skills of teachers of mathematics in the Krasnoyarsk Territory; highlight the professional difficulties of teachers in the subject area “Mathematics”; determine a list of corrective measures to eliminate the identified problems. Methods: theoretical (analysis of scientific literature on the problem of research, systematization and generalization of the results of scientific research) and empirical (ascertaining pedagogical experiment, analysis and interpretation of the results). Results: a program for diagnosing the subject and methodological skills of the professional activity of a mathematics teacher was developed. A diagnostic toolkit has been developed, which is based on the following principles: orientation to current educational results and modern require ments for the labor actions of a teacher, a system activity approach for determining deficiencies in the field of methods of teaching mathematics, the possibility of designing an individual trajectory of a teacher’s professional development based on the results of diagnostics. The analysis of the research results and recommendations for eliminating the identified professional deficiencies are presented. Scientific novelty: developed and substantiated an approach to the formation of control and measuring materials for the diagnosis of professional deficiencies in mathematics teachers. Practical significance: the main results and conclusions of the article can be used to create a regional system for monitoring professional deficits of mathematics teachers, as well as to develop modular training programs for teachers that provide personalized assistance to teachers in eliminating professional difficulties
Keywords: diagnostics of subject and methodological skills, advanced training of mathematics teachers, readiness to solve professional problems.